Szymborska o radości pisania - Gajak-Toczek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The text “Szymborska about the joy of writing” is an attempt to answer the question: “What is poetry for a contemporary poet?” But why only an attempt? one may ask. For this reason that Wisława Szymborska tries to avoid unambiguous answer herself and says that poetry is „a kind of cheerful confusion and troublesome complication, which should bother the followers of traditional divisions.” In her speech during the Nobel Prize awarding ceremony (07.12,1996) Szymborska pointed out that “contemporary poets are skeptical and suspicious even or rather first of all about themselves. They reluctantly declare to be a poets as if it was shame. In our common speech, when we don’t consider each single word, we all use expressions like «ordinary world», «ordinary life», «ordinary course of events» but in the language of poetry, where each single world is crucial, nothing is ordinary or common.”